2012
DOI: 10.1017/s1092852912000417
|View full text |Cite
|
Sign up to set email alerts
|

rTMS age-dependent response in treatment-resistant depressed subjects: a mini-review

Abstract: Results from this study show that low-frequency rTMS over the right DLPFC, with a relatively low number of pulses (420 pulses per session) and a relatively short period of treatment, is effective in the treatment of resistant patients (in a sample also including elderly patients) in a 3-weeks treatment protocol with a low reduction with the progress of age. Furthermore, we found a greater response in younger patients and an inverse correlation between age and treatment response. Adaptations of the protocol acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 32 publications
5
33
0
Order By: Relevance
“…The influence of age on response to nonpharmacological treatment of depression was also reported. Patients at age<60 years had greater response to repetitive transcranial magnetic stimulation compared to older patients (Pallanti et al 2012). On the other hand, our results are in line with data from Amital et al (2012), who found no difference between TRD and non-TRD patients in the prevalence of comorbid somatic disorders, including diabetes, hypertension and ischemic heart disease.…”
Section: Discussionmentioning
confidence: 97%
“…The influence of age on response to nonpharmacological treatment of depression was also reported. Patients at age<60 years had greater response to repetitive transcranial magnetic stimulation compared to older patients (Pallanti et al 2012). On the other hand, our results are in line with data from Amital et al (2012), who found no difference between TRD and non-TRD patients in the prevalence of comorbid somatic disorders, including diabetes, hypertension and ischemic heart disease.…”
Section: Discussionmentioning
confidence: 97%
“…Repetitive transcranial magnetic stimulation (rTMS) entails generation of a focal electromagnetic field by a coil positioned over the scalp, with a course of 20 to 40 sessions. While rTMS does not require anaesthesia and has insignificant cognitive side effects, depressed older people appear to be less responsive than younger adults (Pallanti et al, 2012).…”
Section: Institute For Health and Clinical Excellence In The Uk (Nice mentioning
confidence: 99%
“…Studies including mixed-age samples (see Table 1 for details) have reported mixed results, with some showing an inverse relationship between age and antidepressant efficacy, whereas others have not reported an association. Studies reporting older age to be associated with lesser efficacy need, however, to be interpreted with caution [76,[78][79][80][81][82][83]. For example, two of these RCTs included a small number of participants in the older range (five women ≥ 55 years [76], nine patients ≥ 45 years [79]), which could have biased results.…”
Section: Repetitive Transcranial Magnetic Stimulation (Rtms) Rtms Effmentioning
confidence: 99%
“…In a large open-label study (n=102), Pallanti et al [80] found that older age (≥60 years) was also associated with lesser efficacy. However, the older patients did in fact show a promising response rate of 47 % after treatment (cf.…”
Section: Repetitive Transcranial Magnetic Stimulation (Rtms) Rtms Effmentioning
confidence: 99%